2018
DOI: 10.1038/s41598-018-22243-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional innate immunity restricts Hepatitis C Virus infection in induced pluripotent stem cell–derived hepatocytes

Abstract: Knowledge of activation and interplay between the hepatitis C virus (HCV) and the hosts’ innate immunity is essential to understanding the establishment of chronic HCV infection. Human hepatoma cell lines, widely used as HCV cell culture system, display numerous metabolic alterations and a defective innate immunity, hindering the detailed study of virus-host interactions. Here, we analysed the suitability of induced pluripotent stem cell (iPSC)-derived hepatocyte-like cells (iHLCs) as a physiologically relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…3b). In agreement with a recent study 18 , this suggests that HLCs in general, unlike hepatoma cells, have a functional VLDL biosynthesis pathway. Importantly, pol-HLCs secreted higher levels of lipoproteins than nonpol-HLCs, and these lipoproteins were selectively secreted into the basolateral compartment ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…3b). In agreement with a recent study 18 , this suggests that HLCs in general, unlike hepatoma cells, have a functional VLDL biosynthesis pathway. Importantly, pol-HLCs secreted higher levels of lipoproteins than nonpol-HLCs, and these lipoproteins were selectively secreted into the basolateral compartment ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…2). We and others have previously shown that even nonpol-HLCs can synthesize and release ALB, ApoB100 and ApoE 17,18 . Here, we found that pol-HLCs released the majority of these cargos directionally from their basolateral membrane ( Supplementary Figs.…”
Section: Resultsmentioning
confidence: 82%
“…Modulation of the JAK/STAT pathway has been discussed previously as a way to improve viral replication in HLCs 16–18. Here, we monitored in detail the induction of innate immunity and its influence, on the complete replication cycle over extended periods.…”
Section: Discussionmentioning
confidence: 99%
“…Upon inoculation with cell culture-derived HCV (HCVcc) containing the JFH1 (Gt2a) replication machinery,15 HLCs yield detectable intracellular HCV RNA replication, but only limited and transient production of infectious progeny viruses. It is generally assumed that active innate immunity is responsible for this acute HCV infection 16–18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation